2020
DOI: 10.1038/s41467-019-13907-7
|View full text |Cite
|
Sign up to set email alerts
|

Acidity enhancement through synergy of penta- and tetra-coordinated aluminum species in amorphous silica networks

Abstract: Amorphous silica-aluminas (ASAs) are widely used in acid-catalyzed C-H activation reactions and biomass conversions in large scale, which can be promoted by increasing the strength of surface Brønsted acid sites (BAS). Here, we demonstrate the first observation on a synergistic effect caused by two neighboring Al centers interacting with the same silanol group in flame-made ASAs with high Al content. The two close Al centers decrease the electron density on the silanol oxygen and thereby enhance its acidity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
92
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(96 citation statements)
references
References 72 publications
4
92
0
Order By: Relevance
“…However, the EFAl species generated on zeolite surfaces can easily leach out in liquid-phase reactions, resulting in severe activity loss. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the EFAl species generated on zeolite surfaces can easily leach out in liquid-phase reactions, resulting in severe activity loss. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“… 10 12 In ASAs, the formation of BAS has been widely accepted to originate from an Al atom flexibly coordinated to a neighboring silanol oxygen atom ( Scheme 1 b) 13 15 or via aluminic pseudobridging silanol (PBS-Al, Scheme 1 c, d) at the interface between silica and alumina. 10 , 16 , 17 Zeolite-like bridging Si(OH)Al or replacement of an Al atom by Si in Scheme 1 c (PBS-Si) are also proposed for BAS formation by theoretical calculation studies but lack direct spectral evidence yet. 18 Moreover, alumina domains on ASAs are associated with the formation of Lewis acid sites (LAS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the sustainable energy‐environment challenge, the development of new clean energy from renewable sources has become increasingly important. [ 1–3 ] Solar energy is the most naturally abundant, clean, and sustainable resource. Fujishima and Honda first reported that TiO 2 can achieve effective photoelectrochemical (PEC) water splitting, [ 4 ] which provides an alternative way to produce sustainable hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Solid‐state NMR spectroscopy has become a critical tool for characterizing the active sites on heterogeneous catalysts, capable of providing detailed information on correlation and connectivity of distinct nuclei in a local structure [34–38] . In this work, we established a fundamental understanding of the active sites on Mo/ZSM‐5 for MDA reaction.…”
Section: Introductionmentioning
confidence: 99%